Ginseng polysaccharides ameliorate DSS-induced inflammatory bowel disease by regulating gut microbiota in dogs - Xie, Liuwei; Li, Xiao; Mao, Aipeng; Han, Zhiqiang; Zhang, Xiuli; Liu, Xin; Liu, Qing; Zhao, Weigang; Xu, Chao (Frontiers in Veterinary Science, 2026)
Inflammatory bowel disease (IBD) is a common chronic gastrointestinal disorder in dogs that seriously affects health and quality of life. This study evaluated the effects of ginseng polysaccharides on dextran sodium sulfate (DSS)-induced IBD in dogs, with emphasis on clinical symptoms, serum parameters, and gut microbiota. Our findings revealed that treatment with ginseng polysaccharides alleviated clinical symptoms, improved colonic histopathology, and partially restored serum biochemical changes, including a significant reduction in C-reactive protein. Microbiota analysis showed increased alpha diversity and recovery of community composition, with enrichment of beneficial genera such as Bacteroides, Megamonas, and Fusobacterium, and reduction of Campylobacter. Functional prediction indicated that ginseng polysaccharides reversed DSS-associated suppression of carbohydrate metabolism pathways. These findings suggest that ginseng polysaccharides mitigate DSS-induced IBD in dogs by modulating inflammation and gut microbiota composition, supporting their potential as a natural therapeutic candidate for canine IBD.